In cena: teoria e prática teatral à luz de Vigotski - Silva, Yasmin Carolina Ribeiro (2019)
The present work results from a research developed from 2017 to 2019, as a requisite for obtaining the Master's degree in Psychology. The dissertation entitled In scene: theory and theatrical practice in the light of Vigotski systematizes theoretical contributions of the Russian psychologist Lev Semionovich Vigotski (1896-1934) as a possibility of critical elaboration for theatrical practice and theory. The aim was to make a dialectical and critical reading of Vygotskian works on art and psychology and to establish a dialogue between the fields of Psychology, Education and Theater as important areas of knowledge, besides presenting possibilities to understand psychological processes from a discussion about theatrical art. In addition, we sought to reflect on the exercise of theatrical artist as a particular form of human behavior and to recognize scenic art as a form of language, reflection, knowledge and work, identifying possible contributions of historical-cultural psychology for such. It is a theoretical and conceptual research, that is based on already published materials to elaborate a critical reflection of its own in dialogue with the practical experience of the author as an actress and theater teacher.